Case Report: Severe neutropenia induced by avelumab in a patient with Merkel cell carcinoma - Ohta, Eri; Yamamoto, Kayo; Fujimura, Hitomi; Saito-Sasaki, Natsuko; Okada, Etsuko; Sawada, Yu (Frontiers in Immunology, 2025)
A 78-year-old woman with a history of follicular lymphoma treated with obinutuzumab and bendamustine developed Merkel cell carcinoma (MCC) on her left forearm. After surgical excision, in-transit and lymph node metastases appeared within three weeks. Avelumab and radiotherapy were initiated, but severe neutropenia occurred after two doses, requiring G-CSF support and treatment discontinuation. Despite early cessation, metastatic lesions regressed. This case suggests that prior B-cell–directed therapy may increase the risk of hematologic toxicity with immune checkpoint inhibitors and that even short-term avelumab may induce a durable response in MCC.